"Eating, laughing, and tonic seizing", that is a laughter‐induced syncope in elderly. Issue 1 (28th December 2020) - Honda, Masayuki; Shimotake, Akihiro; Hitomi, Takefumi; Kuzuya, Akira; Takahashi, Ryosuke; Ikeda, Akio
Abstract: Laughter‐induced syncope is a rare syndrome with good prognosis, but not widely known by health care providers. We had a patient who had whole body "freezing" episodes immediately after laughing vigorously during meals. Epilepsy was ruled out and diagnosis of laughter‐induced syncope was made. Severe cerebral hypoperfusion and relatively disinhibited brain stem function may account for tonic posturing. It should be considered as a differential diagnosis in patients presenting whole body "freezing" episodes after big laughter, along with tonic seizure, gelastic seizure and cataplexy. Detailed and precise inquiry is helpful in correct diagnosis and could prevent from repeated events with unnecessary antiseizure medication.